Anatomical variations in coronary venous drainage: Challenges and solutions in delivering cardiac resynchronization therapy. (13th May 2022) - Akhtar, Zaki; Sohal, Manav; Kontogiannis, Christos; Harding, Idris; Zuberi, Zia; Bajpai, Abhay; Norman, Mark; Pearse, Simon; Beeton, Ian; Gallagher, Mark M.
Abstract: Aims: To investigate the abnormalities of the coronary venous system in candidates for cardiac resynchronization therapy (CRT) and describe methods for circumventing the resulting difficulties. Methods: From four implanting institutes, data of all CRT implants between October 2008 and October 2020 were screened for abnormal cardiac venous anatomy, defined as an anatomical variation not conforming to the accepted 'normal' anatomy. Patient demographics, procedural detail, and subsequent left ventricle (LV) lead pacing indices were collected. Results: From a total of 3548 CRT implants, 15 (0.42%) patients (80% male) of 72.2 ± 10.6 years in age with an LV ejection fraction of 34 ± 10.3% were identified to have had an abnormal cardiac venous anatomy over the study period. There were 13 cases of persistent left side superior vena cava (pLSVC), five of which had coronary sinus ostium atresia (CSOA) including two with an "unroofed" coronary sinus (CS); one patient had a unique anomalous origin of the CS and one patient had an isolated CSOA. In total 14 patients (60% repeat attempt) had successful percutaneous implant under general anesthesia (46.7%) via the cephalic vein (59.1%), using the femoral approach (53.3%) for levophase venography and/or pull‐through, including one case of endocardial LV implant. Pacing follow‐up over 37.64 ± 37.6 months demonstrated LV lead threshold between 0.62 and 2.9 volts (pulsewidth 0.4–1.5 ms) in all cases; five patients died within 2.92 ± 1.6 years of a successful implant. Conclusion: CRT devices can be implanted percutaneously even in the presence of substantial abnormalities of coronary venous anatomy. Alternative routes of venous access may be required.